Analysis of A Decision Support System for the Selection of the Best Coffee Supplier at Arion Coffee Using AHP - Diva Anjeliansyah Putri; Wahit Desta Prastowo (Journal of Computing Innovations and Emerging Technologies, 2025)
This study aims to determine the best coffee supplier for Arion Coffee using the Analytical Hierarchy Process (AHP) as a structured multi-criteria decision-making approach. The evaluation involves four key criteria price, quality, delivery timeliness, and service with three supplier alternatives: Kopi Nusantara (SUP A), Java Beans Supply (SUP B), and Tropical Roast Indonesia (SUP C). Data were collected through interviews and expert evaluations from Arion Coffee’s procurement team. The AHP method was used to assign weights to each criterion, conduct pairwise comparisons, and calculate consistency ratios. Results indicate that quality holds the highest importance (0.623), followed by price (0.216), delivery timeliness (0.106), and service (0.055). Based on the overall synthesis, Tropical Roast Indonesia (SUP C) achieved the highest score (0.441), followed by Java Beans Supply (0.337) and Kopi Nusantara (0.214). The findings highlight that coffee bean quality is the dominant factor influencing supplier selection, reflecting Arion Coffee’s priority on maintaining product excellence over cost efficiency. The application of AHP provides a rational and objective framework for supplier evaluation, improving decision accuracy and reducing subjectivity.